ANALISIS KELAYAKAN FINANSIAL AGROINDUSTRI PENGOLAHAN ONGGOK UBI KAYU DI KECAMATAN TERUSAN NUNYAI KABUPATEN LAMPUNG TENGAH - Prayogi, Bagoes; Abidin, Zainal; Gitosaputro, Sumaryo (Lampung University, 2020)
The aims of this research are to analyze the financial feasibility and the sensitivity of cassava solid waste processing agroindustry. The research was conducted in March 2018 in Terusan Nunyai District, Lampung Tengah Regency by purposeive selected. The sampels of the research were 2 cassava solid waste processing agroindustry. Research data were analyzed by using financial feasibility and sensitivity analysis method. The results showed that cassava solid waste processing agroindustries were financially profitable and feasible to be developed. The value of NPV in two agroindustries were bigger than 0. The Value of Net B/C and Gross B/C in two agroindustries were bigger than 1. The value of IRR on two agroindustries more than commercial interest rate, and payback period of investmens could be covered less than the ages of agroindustries. The sensitivity value showed that processing cassava solid waste processing agroindustries was sensitive if there was an increase in costs of 3.25 percent. Most of criteria in all agroindustries was sensitive if there was a decrease in production volume of 5 percent. All agroindustries was sensitive if there was a decrease in price of 3.25 percent. Key words : Cassava solid waste, Feasible, Sensitivity